2011
DOI: 10.3758/s13428-011-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the accuracy of the retrospective recall method used in expertise research

Abstract: Expertise typically develops slowly over years, and controlled experiments to study its development may be impractical. Researchers often use a correlational, retrospective recall method in which participants recall career data, sometimes over many years before. However, recall accuracy is uncertain. The present study investigated the accuracy of recalled career data for up to 38 years, in over 600 international chess players. Participants' estimates of their entry year into international chess, total career g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Fourthly, many studies used retrospective measures which may make them susceptible to recall bias. This can limit validity, if there is a long gap between the event and recall (Howard, 2011). However, this may not have been an issue as only recent adult stressful life events were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, many studies used retrospective measures which may make them susceptible to recall bias. This can limit validity, if there is a long gap between the event and recall (Howard, 2011). However, this may not have been an issue as only recent adult stressful life events were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal onboarding time frame may have become compressed and warrants further examination given changes in the nature of the employment relationship (e.g., Rousseau, ), increased employee mobility, and use of contingent work arrangements. In terms of reliance on recall, it has been demonstrated that retrospective reports can be biased (e.g., Howard, ), yet research also suggests that they can be fairly accurate and are generally not so imperfect as to be invalid (e.g., Todd, Tennen, Carney, Armeli, & Affleck, ). The newcomer is the best source for information about their experiences, but collecting this information in closer proximity to the onboarding practices in question would help reduce this concern.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also continue the search for objective measures to describe the developmental pathways leading to expertise. Retrospective recall has been questioned as a means for obtaining verifiable data (Howard, 2011), but at the present time better alternatives have yet to be widely adopted. For disability sport athletes, self-report approaches might also be vulnerable to more inaccuracy or inconsistency regarding certain topics.…”
Section: Discussionmentioning
confidence: 99%